The Sacred Community: Art, Sacrament, and the People of God. By David Jasper - Johnson, Bradley A. (Literature and theology, 2014)
In this handsomely packaged and composed book David Jasper concludes his multi-volume hermeneutical examination of the sacred. Where in the first volume, The Sacred Desert (2004), Jasper focuses on the history of literary and visual art that has emerged from (and in some senses re-rehearses) mystical experiences, with special emphasis on these works’ recurring desert locale; and in the second volume, The Sacred Body (2009), its embodiment in an earthy, and perhaps even carnal asceticism, highlighting in particular the blessing that is the body’s finitude and frailty; in The Sacred Community he reflects in a series of essays on the sacramental necessity of communal enactment.